E-078 Acute stroke intervention with solitaire stent: a meta-analysis. (4th July 2012) - Dumont, T; Kass-Hout, T; Eller, J; Siddiqui, A; Levy, E
Abstract : Introduction: Based on promising revascularization results in the SWIFT trial (83% revascularization), FDA approval of the Solitaire stent for acute stroke intervention is anticipated. The Solitaire stent has been used extensively in Europe for acute stroke intervention. This important real-world use case experience provides insight into the applicability of Solitaire for post-market use. The purpose of this study is to review existing case series of stroke intervention with Solitaire to evaluate efficacy in revascularization and outcomes. Method: A meta-analysis of existing case series with acute stroke intervention employing the Solitaire stent was performed. Case series were identified using a thorough literature review. All case series (including case reports) were included. Endpoints including recanalization and Modified Rankin Score on discharge were noted. Results: Twelve studies were identified with at least one acute stroke intervention with the Solitaire stent. These studies included a total of 205 patients. Revascularization was successfully performed in 182 patients (89%). Acceptable outcomes (MRS 0–2) were reported for 100 patients (49%). Conclusions: With the anticipated approval of the Solitaire stent for publication of the SWIFT trial in a few months, "real world" case series such as this will soon be of less relevance. In itself, this relatively small series has little to offer in comparison to the similar reports cited. In addition, several more similar case series have been published since the writing of this manuscript (by my count at least seven more series are available on PubMed). At the very least, these articles should be considered in a revision prior to re-submission. Competing interests: T Dumont: None. T Kass-Hout: None. J Eller: None. A Siddiqui: Grants: University at Buffalo, National Institutes of Health (not for this study). Codman & Shurtleff, Concentric Medical, ev3/Covidien Vascular Therapies, GuidePoint Global Consulting, Penumbra;. Financial interests: Hotspur, Intratech Medical, StimSox, Valor Medical; Speakers' Bureaus: Codman & Shurtleff, Genentech; Honoraria: Abbott Vascular, Genentech, Neocure Group, Annual Peripheral Angi. E Levy: Grant, other research support, research support: Codman & Shurtleff, Inc., ev3/Covidien Vascular Therapies. consultant/advisory board: Codman & Shurtleff, Inc.; Consultant per project and/or per hour: Codman & Shurtleff; ev3/Covidien Vascular Therapies, TheraSyn Sensors. ownership interests: Intratech Medical, Mynx/Access Closure; honoraria: Boston Scientific; fees for carotid stent training: Abbott Vascular, ev3/Covidien Vascular Therapies. Receives no consulting salary.